2015
DOI: 10.1186/s12935-015-0178-0
|View full text |Cite
|
Sign up to set email alerts
|

PBK/TOPK mediates geranylgeranylation signaling for breast cancer cell proliferation

Abstract: PDZ binding-kinase (PBK) (also named T-lymphokine-activated killer cell-originated protein kinase (TOPK)), a serine/threonine kinase, is tightly controlled in normal tissues but elevated in many tumors, and functions in tumorigenesis and metastasis. However, the signaling that regulates expression of PBK in cancer cells remains elusive. Here we show that atorvastatin (Lipitor), an inhibitor of hydroxymethylglutaryl co-enzyme A (HMG-CoA) reductase that is a rate-limiting enzyme of mevalonate pathway, down-regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 37 publications
1
41
0
Order By: Relevance
“…Depletion of cell cycle regulators can cause radiosensitisation ( Ayllon and O'Connor, 2007 ; Dou et al , 2015 ; Lei et al , 2015 ). In support of this argument, cell cycle regulatory kinases including CDC2, ATM, CDKN2B, CDK5R1 and PLK4 were highly ranked in the screen that identified TOPK ( Tiwana et al , 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of cell cycle regulators can cause radiosensitisation ( Ayllon and O'Connor, 2007 ; Dou et al , 2015 ; Lei et al , 2015 ). In support of this argument, cell cycle regulatory kinases including CDC2, ATM, CDKN2B, CDK5R1 and PLK4 were highly ranked in the screen that identified TOPK ( Tiwana et al , 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Actually, TOPK is upregulated upon activation of insulin-like growth factor 1 (IGF1) signaling [ 34 ]. It is reported to be the target gene of Hippo-YAP signaling [ 35 ] and EWS-FLI1pathway [ 36 ]. Expression of TOPK is regulated by cell cycle-specific transcription factors c-Myc, E2F [ 37 ] and CREB/ATF [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study identified PBK as a downstream target of Hippo/YAP signaling [24], so we examined total and phospho-YAP levels in parental and PBK KO U2OS cells to determine if loss of PBK would affect the status of YAP. We found no noticeable changes to the total YAP protein level, nor did we see any changes to phosphorylation levels at S127 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A recent report uncovered that PBK expression is regulated by Yes-associated protein (YAP), a transcriptional co-activator of the Hippo pathway [22,23], and is responsive to geranylgeranyl signaling in ER- breast cancer cells [24]. In this report, we identified additional CDK1/cyclin B phosphorylation sites on PBK and elucidate the role of the CDK1/PBK axis in breast cancer.…”
Section: Introductionmentioning
confidence: 85%